Dog days - Gendry-Kim, Keum Suk (Drawn & Quarterly, a client publisher of Farrar Straus & Giroux, 2024)
"Yuna never wanted to adopt a dog. But with her partner in mourning - and in desperate need of a boost in morale - she gives in to his humble request. And in the grand tradition of reluctant pet owners, she and their puppy soon become inseparable. The young couple even goes so far as to relocate to soothe their new canine pal's anxiety. After all, there's nothing like a move to the country to set yourself right. Right?"--